2019
DOI: 10.5603/cj.a2018.0008
|View full text |Cite
|
Sign up to set email alerts
|

Implantable loop recorders in patients with unexplained syncope: Clinical predictors of pacemaker implantation

Abstract: Background: Implantable loop recorders (ILR) are a valuable tool for the investigation of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 43 publications
5
12
0
Order By: Relevance
“…Therapeutic interventions were common after ICM placement for unexplained syncope, as more than 28% of the patients in our cohort underwent an intervention within 2 years of ICM follow-up. This is consistent with data from several studies reporting that approximately one in four syncope patients monitored by ICM for 1–3 years receive a pacemaker, implantable cardioverter-defibrillator, or have an ablation performed [ 9 , 12 , 13 ]. The reduction in acute events observed during the follow-up was presumably driven by the administration of therapeutic interventions.…”
Section: Discussionsupporting
confidence: 90%
“…Therapeutic interventions were common after ICM placement for unexplained syncope, as more than 28% of the patients in our cohort underwent an intervention within 2 years of ICM follow-up. This is consistent with data from several studies reporting that approximately one in four syncope patients monitored by ICM for 1–3 years receive a pacemaker, implantable cardioverter-defibrillator, or have an ablation performed [ 9 , 12 , 13 ]. The reduction in acute events observed during the follow-up was presumably driven by the administration of therapeutic interventions.…”
Section: Discussionsupporting
confidence: 90%
“…Comparing to the results of other authors, in our study fewer patients had symptomatic episodes with no arrhythmic abnormalities detected by ILR (Huemer et al, 2019; Kabra et al, 2009). In such cases, the role of ILR is to exclude arrhythmia as primary cause of syncope or palpitations, and the final diagnosis is usually made by a neurologist (in our study, eight patients had unrecognized epilepsy, two psychogenic non‐epileptic seizures, and in six, prolonged neurological monitoring was indicated).…”
Section: Discussionsupporting
confidence: 65%
“…Thus, the present study cohort consisted mainly of patients without severe structural heart disease. Previous studies have identified the following risk factors for clinically relevant arrhythmia: age, female gender, syncope with injury sequelae, obesity and impaired renal function 8–11 . Older age was also associated with a higher incidence of the primary endpoint in our study (Table 1).…”
Section: Discussionsupporting
confidence: 58%
“…Previous studies demonstrated the usefulness of ILR as a major diagnostic tool, based on the advantage of extended ECG monitoring, in diagnosing unexplained syncope 3–7 . In the past, several clinical characteristics with an association to arrhythmia were identified 7–16 . Nevertheless, data of ILR are still limited and large studies that examined predictors of arrhythmias are rare.…”
Section: Introductionmentioning
confidence: 99%